Dynamic effects of sleep deprivation on emotional behavior, circadian rhythm genes, and inflammatory infiltration in the medial prefrontal cortex - Cao, Dandan; Geng, Xue; Yi, Shaoqiong; Zhang, Haifeng; Fu, Yong (Frontiers in Behavioral Neuroscience, 2026)
BackgroundSleep, a core circadian rhythm, maintains physiological homeostasis. Its dysfunction links to neuropsychiatric disorders. Clinically, poor sleep impairs positive emotions and enhances negative emotion susceptibility, but the mechanism remains unclear, potentially involving circadian clock genes and neuroinflammatory pathways.MethodsDivide the male C57BL/6J mice into the following five groups: Non-sleep deprivation (SD) control (CON), sleep recovery 14-day after SD 7-day (SD7R14), sleep recovery 21-day after SD 7-day (SD7R21), sleep recovery 14-day after SD 14-day (SD14R14), and sleep recovery 21-day after SD 14-day (SD14R21). Behavioral tests evaluated anxiety-like behaviors, fear and andanhedonia. Histological staining observed neuronal morphology in the medial prefrontal cortex (mPFC), and RT-qPCR was employed to measure mRNA levels of circadian clock genes, Silent information regulator 6 (Sirt6), High mobility group box-1 (Hmgb1), and inflammatory factors.ResultsSD induces time-dependent anxiety-like behaviors (reduced exploratory activity in elevated mazes), anhedonia (decreased sucrose preference), and fear behaviors (prolonged immobility in forced swim and tail suspension tests). Histological analysis reveals reversible neuronal damage in the mPFC, with complete recovery observed after 21 days of sleep restitution. Molecular analyses show dysregulation of the muscle aryl-hydrocarbon receptor nuclear translocator-like 1 (Bmal1) and circadian locomotor output cycles kaput (Clock) circadian pathway and activation of the Sirt6/Hmgb1 inflammatory axis, leading to proinflammatory cytokine release (TNFα, IL1β, COX-2, IL6), with partial recovery after sleep restoration.ConclusionSD for 7-day or 14-day may impair emotional behaviors by disrupting the RNA expression of clock genes and the Sirt6/Hmgb1 inflammatory axis, while sleep recovery for 14-day or 21-day can partially reverse this impairment.